Forgery, market liquidity, and demat trading: Evidence from the national stock exchange in India - Madhav S. Aney; Sanjay Banerji (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We analyse the impact of the introduction of a new technology on the National Stock Exchange in India that allowed trading of stocks without the need to transfer paper share certificates (demat trading). We document a decrease in the bid-ask spread and an increase in trading volume following its introduction particularly for those stocks that were previously illiquid. We present evidence that suggests that the primary channel for the increase in liquidity was the elimination of the risk of being sold forged securities as the clearing system took on the risk of reimbursing buyers of forged shares at the introduction of demat trading.
urn:nbn:fi-fe2024053041567
Keywords: G18; G19; G28; 330; Liquidity trading; Bid-ask Spead; Frauds; Market manipulations